2015
DOI: 10.1260/0144-5987.33.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Solar Pv/Wind/Diesel Hybrid Power System for a Remotely Located Population near Arar, Saudi Arabia

Abstract: Different hybrid configurations of wind, photovoltaic (PV), and diesel systems for a village in the north-eastern region of Saudi Arabia are presented. The configurations (i) diesel only, (ii) wind-diesel, (iii) PV-diesel, and (iv) wind-PVdiesel power generation systems are designed and compared to select the optimal alternative system by considering the minimum cost of energy and least environmental impact. For sizing and optimizing the hybrid power systems, local hourly average wind speed, hourly total solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 84 publications
(88 reference statements)
0
29
0
Order By: Relevance
“…Saudi Arabia observes high values of global solar radians and long sunshine duration throughout the year [25,26]. The solar energy has been proved to be technologically and economically feasible in Saudi Arabia in particular [27,28] and in the region in general. In this paper, a feasibility analysis of a solid desiccant cooling system operating in conjunction with an evaporative cooler is carried out for five cities of Saudi Arabia.…”
Section: System Descriptionmentioning
confidence: 99%
“…Saudi Arabia observes high values of global solar radians and long sunshine duration throughout the year [25,26]. The solar energy has been proved to be technologically and economically feasible in Saudi Arabia in particular [27,28] and in the region in general. In this paper, a feasibility analysis of a solid desiccant cooling system operating in conjunction with an evaporative cooler is carried out for five cities of Saudi Arabia.…”
Section: System Descriptionmentioning
confidence: 99%
“…Hence to supplement the energy needs of these areas through wind and solar photovoltaics, techno-economic studies were conducted and possibility of renewable energy penetration was assessed. It was concluded that 25 to 35% renewable energy penetration could be achieved with the existing diesel power stations [39][40][41][42][43][44][45].…”
Section: Saudi Arabia's Wind Power Research and Development Updatementioning
confidence: 99%
“…The electricity shortfall during summer reaches about 4000 MW to 5000 MW [2], which is alarming. Solar energy is being utilized globally in many applications such as zero energy and sustainable villages [3], PV irrigation [4,5], solar thermal systems [6], PV power plants for small loads [7,8], grid-connected multi-megawatt-sized PV power plants [9,10], solar cooling systems [11], solar water heating systems for industrial applications [12], PV water pumping [13,14], PV energy for desert camping [15], and solar energy utilization and hybrid power systems for remote locations [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%